Common and distinct functions of mouse Dot1l in the regulation of endothelial transcriptome - Yoo, Hyunjin; La, Hyeonwoo; Park, Chanhyeok; Yoo, Seonho; Lee, Hyeonji; Song, Hyuk; Do, Jeong Tae; Choi, Youngsok; Hong, Kwonho (Frontiers in Cell and Developmental Biology, 2023)
Epigenetic mechanisms are mandatory for endothelial cells (ECs) during cardiovascular development. Dot1l-mediated gene transcription in mice is essential for the development and function of lymphatic ECs (LECs). The role of Dot1l in the development and function of blood ECs (BECs) is unclear. RNA-seq datasets from Dot1l-depleted or -overexpressing BECs and LECs were used to comprehensively analyze regulatory networks of gene transcription and pathways. Dot1l depletion in BECs changed the expression of genes involved in cell-to-cell adhesion and immunity-related biological processes. Dot1l overexpression modified the expression of genes involved in different types of cell-to-cell adhesion and angiogenesis-related biological processes. Genes involved in specific tissue development-related biological pathways were altered in Dot1l-depleted BECs and LECs. Dot1l overexpression altered ion transportation-related genes in BECs and immune response regulation-related genes in LECs. Importantly, Dot1l overexpression in BECs led to the expression of genes related to the angiogenesis and increased expression of MAPK signaling pathways related was found in both Dot1l-overexpressing BECs and LECs. Therefore, our integrated analyses of transcriptomics in Dot1l-depleted and Dot1l-overexpressed ECs demonstrate the unique transcriptomic program of ECs and the differential functions of Dot1l in the regulation of gene transcription in BECs and LECs.